Immunohistochemical characterization of renal tumors in patients with Birt‐Hogg‐Dubé Syndrome. (19th January 2015) - Iribe, Yasuhiro; Kuroda, Naoto; Nagashima, Yoji; Yao, Masahiro; Tanaka, Reiko; Gotoda, Hiroko; Kawakami, Fumi; Imamura, Yoshiaki; Nakamura, Yasushi; Ando, Midori; Araki, Akinobu; Matsushima, Jun; et al.
<x xml:space="preserve">Abstract</x> Birt‐Hogg‐Dubé syndrome (BHD) is an autosomal dominant disorder associated with a germline mutation of folliculin (FLCN). The affected families are at a high risk for developing multiple renal cell carcinomas (RCC). Little is known about the immunostaining patterns of mutant FLCN‐associated RCCs. We investigated 32 RCCs obtained from 17 BHD patients. The studied tumors included chromophobe RCCs (n = 15), hybrid oncocytic/chromophobe tumors (HOCT) (n = 14) and clear cell RCCs (n = 3). Almost all chromophobe RCCs and HOCTs revealed positive staining for S100A1, Ksp‐cadherin and CD82. They stained either focally or diffusely for CK7, and were negative for CA‐IX. All clear cell RCCs were positively stained for CA‐IX and negative for CK7. These data confirmed that mutant FLCN‐associated oncocytic and clear cell RCCs exhibited generally similar immunostaining patterns compared to their sporadic counterparts. Frequent positive staining for S100A1, Ksp‐cadherin and CD82 in chromophobe RCCs and HOCTs indicated that these two types were relatively similar rather than distinctively different in their patterns of immunoreactivity. Characteristic peri‐nuclear halos and polygonal cells with clear cytoplasm, which often misleads pathologists into the diagnosis of clear cell RCC, should be carefully examined using an immunohistochemical panel including CA‐IX, Ksp‐cadherin, CD82 and CK7.